Analyzing students’ epistemic actions in basic algebra using the Abstraction in Context (AiC) model: A descriptive qualitative case study - Munawwaroh, Alda Gemellia; Pramudya, Ikrar; Siswanto, Siswanto (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Mathematical abstraction skills, which include concept recognition, relationship development, and new knowledge formation, are necessary for understanding basic algebra. The abstraction process can be analyzed through students' epistemic actions using the AiC Model, which helps identify how students recognize, develop, and actively construct mathematical concepts. This study aims to explore and describe the epistemic actions of seventh-grade students in performing mathematical abstraction, thereby providing insights that can be used to develop more effective algebra teaching strategies. The results show that only S1 was able to effectively apply epistemic actions in mathematical abstraction, even though this student had not yet reached the stage of constructing new knowledge. Meanwhile, other students experienced difficulties, especially in recognizing incorrect knowledge structures and performing constructing and building actions. These difficulties were largely due to incomplete algebraic knowledge, which prevented students from using theoretical thinking effectively and reorganizing their knowledge. Based on these findings, teachers are advised to emphasize a deep conceptual understanding of algebra rather than memorization. In addition, the use of contextual and visual representations should be strengthened to help students connect concrete and abstract concepts. Teachers can also design progressive tasks that guide students through recognition, relationship building, and systematic knowledge construction.